2021
DOI: 10.1111/iej.13604
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre‐operative submucosal administration of dexamethasone, tramadol, articaine on the success rate of inferior alveolar nerve block on mandibular molars with symptomatic irreversible pulpitis: A randomized, double‐blind placebo‐controlled clinical trial

Abstract: Aim: To establish the effects of submucosal tramadol, dexamethasone and articaine on the success of inferior alveolar nerve blocks (IANB) during root canal treatment of mandibular molars with symptomatic irreversible pulpitis (SIP). Methodology:In this randomized double-blind, controlled clinical trial, 120 patients with the diagnosis of SIP in their mandibular first or second molars were included and randomly divided into four groups (n = 30). The control group received normal saline and three experimental gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 44 publications
(70 reference statements)
0
23
0
Order By: Relevance
“…In total, 17 clinical assays were found in both databases ( Figure 1 ), of which 14 obtained a low or medium risk-of-bias result according to the Cochrane Collaboration’s risk-of-bias tool ( Figure 2 ). In this way, 14 clinical trials [ 8 , 9 , 10 , 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] were used to perform the qualitative analysis, and 11 were used for the quantitative assessment [ 8 , 9 , 11 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 17 clinical assays were found in both databases ( Figure 1 ), of which 14 obtained a low or medium risk-of-bias result according to the Cochrane Collaboration’s risk-of-bias tool ( Figure 2 ). In this way, 14 clinical trials [ 8 , 9 , 10 , 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] were used to perform the qualitative analysis, and 11 were used for the quantitative assessment [ 8 , 9 , 11 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The anesthetic success was evaluated across eight clinical trials that compared dexamethasone and placebo in patients with SIP [ 8 , 9 , 11 , 14 , 16 , 17 , 20 , 21 ]. The qualitative analysis showed that five clinical investigations presented statistical differences in favor of dexamethasone when compared to placebo [ 8 , 9 , 14 , 20 , 21 ], while three articles found no statistical difference between dexamethasone and placebo [ 11 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations